Strategic Communications in Counteracting Destructive Russian Narratives - Aulin Oleksandr; Aulina Olena (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2023)

(untitled)
The article examines strategic communications carried out by Ukraine, using the available information resources in the context of combating Russian narrative constructions. The foreign and Ukrainian experts’ approaches to the definition of the term strategic communications are considered. An analysis of the use of narrative structures in the context of negative Russian influence on Ukraine’ information space was carried out. Organizational and other measures carried out by Ukrainian participants in strategic communications in the context of countering Russian Federation destructive informational influence were studied. Recommendations for increasing the effectiveness of Ukraine’s strategic communications are given, in particular through the use of libraries additional capabilities. According to the logic of the research, a comparative method was applied (in particular, to compare different approaches to understanding strategic communications), methods of sociology and political science, as well as expert evaluations (during the study of the essential characteristics of Russian narratives and opposition to them from the Ukrainian side). As a result, in particular, it was found that the Russian Federation is characterized by a mostly aggressive focus on promoting or changing cultural values in the minds of target audiences through the use of appropriate narratives. At the same time, the West is gradually moving from considering strategic communications in the context of rivalry towards their perception as a means of con structive communication. Russian aggression, the active phase of which has been ongoing since 2014, prompts Ukrainian experts and political circles to consider strategic communications primarily within the framework of countering the Russian Federation’ destructive informational influence, and one of its the most important elements is mentioned narrative constructions. The overall effectiveness of strategic communications increases in the case of complex and systematic use of the capabilities of state and non state actors, with an appropriate level of overall coordination.